2003
DOI: 10.1523/jneurosci.23-33-10593.2003
|View full text |Cite
|
Sign up to set email alerts
|

Kalirin, a Multifunctional Rho Guanine Nucleotide Exchange Factor, Is Necessary for Maintenance of Hippocampal Pyramidal Neuron Dendrites and Dendritic Spines

Abstract: The structures of dendritic spines and the dendritic tree, key determinants of neuronal function, are regulated by diverse inputs that affect many scaffolding and signaling molecules. Nevertheless, here we show that reduced expression of a single gene results in loss of dendritic spines and a decrease in dendritic complexity. Kalirin, a dual Rho GDP-GTP exchange factor, causes spine formation when overexpressed. Reduced expression of Kalirin in CA1 hippocampal neurons resulted in a reduction in linear spine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
185
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(190 citation statements)
references
References 57 publications
2
185
0
3
Order By: Relevance
“…For example, the NR2B-associated Rac-GTP exchange factor (GEF) Tiam1 leads to Rac activation and spine growth in response to NMDA-receptor stimulation (14). Two other previously characterized GEFs, kallirin and intersectin, are recruited by EphB receptors, activate Rac and Cdc42, and thereby promote the formation of dendritic protrusions (25)(26)(27). ␣1-Chimaerin might act to counterbalance such activities by inactivating Rac1 and thereby limiting the growth of dendritic arbors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the NR2B-associated Rac-GTP exchange factor (GEF) Tiam1 leads to Rac activation and spine growth in response to NMDA-receptor stimulation (14). Two other previously characterized GEFs, kallirin and intersectin, are recruited by EphB receptors, activate Rac and Cdc42, and thereby promote the formation of dendritic protrusions (25)(26)(27). ␣1-Chimaerin might act to counterbalance such activities by inactivating Rac1 and thereby limiting the growth of dendritic arbors.…”
Section: Discussionmentioning
confidence: 99%
“…LIM kinase knock-out mice also show abnormalities in spine morphology and PSDs (Meng et al, 2002). More recently, it was found that ephrinB receptors, through translocation of kalirin and activation of Rac1 and PAK1, markedly promoted dendritic spine morphogenesis during development (Penzes et al, 2003), whereas, conversely, reduced expression of kalirin decreased spine density (Ma et al, 2003). Interestingly, the phenotype observed here with PAK3 suppression or dominant-negative PAK3 resembles very much the phenotype associated with expression of a dominant-negative mutant of GIT1 that results in mislocalized activation of Rac1 (Zhang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the filopodia-like protrusions induced by PAK3 dominant-negative mutation were devoid of postsynaptic densities or expressed only very small PSDs and/or lacked presynaptic partners. It is interesting in this respect that Rac1 signaling has also been implicated in receptor aggregation at inhibitory interneurons (Meyer et al, 2000) and that reduced kalirin expression was associated with a redistribution of PSD markers, as well as elimination of presynaptic endings (Ma et al, 2003). Furthermore, in Drosophila, PIX mutation is associated with defects in the stabilization of postsynaptic structures, an effect that involves a PAK homolog (Parnas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in rodents, kalirin-7 protein levels are almost undetectable at birth, only increasing at postnatal day 14, which coincides with the onset of synaptogenesis [73,74]. Kalirin-7 plays a key role in the regulation of the size and density of dendritic spines, where it interacts with several PDZ domain-containing proteins [64][65][66][67][68].…”
Section: Kalirin-7mentioning
confidence: 99%